Improving Scientific Article Writing Skills among Civil Engineering Students through a Journal Writing Workshop - Louise Elizabeth Radjawane; Luciana Buarlele; Irwan Lie Keng Wong; Sufiati Bestari; Helen Adri Irene Sopacua; Hanna Mariani Singgih; Lasty Dinulfy RKS (Carmin: Journal of Community Service, 2026)
The lack of understanding of students in writing journal articles, the use of repetitive sentences and inappropriate terms in the field, as well as the high plagiarism rate results in poor quality articles. Through community service activities, namely journal article writing workshops, it is hoped that academic skills in journal writing, understanding the use of reference manager applications and plagiarism can be improved. The practice by learning method is used in this activity, thus that students are able to directly apply the material presented. The results of this activity, students are able to write scientific journal articles following writing rules/templates, organize and group relevant citations, create citation maps, connect the Researchrabbit application to Zotero and Mendeley, and the plagiarism score using Turnitin is a maximum of 20%. The combination of providing workshop and mentorship in journal writing to students has been proven to enhance students' understanding and ability in scientific journal writing.